Axiology of law in civil society - S. G. Pevko (Law and Safety)
The issue of the existence of law in society is considered through the definition of its value. The components that reveal the main issue of the research topic have been studied in detail. The study of each component of the problem under investigation determines the prerequisites for the existence and effectiveness of the impact of legal norms on society, which reflects the main purpose of law and its axiology in civil society. These components are the building blocks that make it possible to comprehensively explore the issues of the article.